Peculiarities of productivity formation of the genus Salix L. representatives - В. В. Баликіна (Plant Varieties Studying and Protection)
Purpose. To identify the productivity of the genus Salix L. plants and study the relationship between its structural elements. Methods. Field study, laboratory analysis, analytical approach.